Liu Wei - Luard, Honey 19XX- (White Cube Gallery, 2015)
Part of a new generation in China that grew up in a period of urban expansion, Liu Wei has frequently turned to urban themes in his work. He alters and reassembles detritus found on building sites - such as metal piping, wooden slats, old doors and large sheets of canvas - into highly complex sculptural and architectural installations